Analisis Yuridis terhadap Perjanjian Utang Piutang Antara Para Pihak untuk Kepentingan Pilkada: Studi Putusan Pengadilan Negeri Kalabahi Nomor : 21/Pdt.G /2017 /PN.Klb Ditinjau dari KUHPerdata - Alif Marwan Fahim Nampira; Yossie M. Y. Jacob; Husni Kusuma Dinata (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
The purpose of this research is to find out To find out how the debt and credit agreement between the parties for the benefit of the election (Study of the Kalabahi District Court Decision Number 21/Pdt.G /2017 /PN.Klb) Reviewed from Kuhperdata and what are the legal consequences of the debt and credit agreement (Study of the Kalabahi District Court Decision Number 21/Pdt.G /2017 /PN.Klb) Reviewed from Kuhperdata. Benefits Provides a contribution to develop insights in legal science on the settlement of defaults in oral debt and credit agreements in the Kalabahi District Court Decision Number 21/Pdt.G /2017 /PN.Klb). This research is a type of Normative research. The results of this study show: (1) the debt and credit agreement between the parties for the benefit of the election (Study of the Decision of the Kalabahi District Court Number 21/Pdt.G /2017 /PN.Klb) Reviewed from Kuhperdata is that it does not have a legal relationship that occurs by the two parties because there is no agreement as contained in article 1320 of the Civil Code so that it does not provide a legal relationship by the two parties which makes the agreement invalid. (2) the legal consequences of the debt agreement (Study of the Decision of the Kalabahi District Court Number 21/Pdt.G /2017 /PN.Klb) Reviewed from Kuhperdata, namely the legal consequences received by the parties are that the agreement can be canceled because it does not comply with the applicable provisions, namely in article 1320 of the Civil Code. Although article 1338 of the Civil Code binds the parties and applies as law to them, the basis for the validity of article 1338 is seen from article 1320 of the Civil Code to determine whether the agreement is valid or not, so it is clear that the two parties have no legal relationship and the agreement can be canceled.